The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1108/17538371211235272
|View full text |Cite
|
Sign up to set email alerts
|

Boundary action in construction projects: new collaborative project practices

Abstract: PurposeTraditional construction project practice has been based on rigid and impermeable boundaries that have made communication, cooperation and integration a major challenge. However, new collaborative approaches have been developed. This paper aims at adding to knowledge on projects‐as‐practice by interpreting findings from a case study on a contemporary collaborative construction project. The purpose of this paper is to provide knowledge about organizational development in the project‐based construction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Construction project organizations thus often become disconnected from the company level and hard to manage and integrate throughout the process, from drawings to finished building. Gadde, 2000, 2002;Karrbom Gustavsson and Gohary, 2012;Karrbom Gustavsson and Hallin, 2015;Kristiansen, et al, 2005;London and Kenley, 2001) Dubois and Gadde (2002) characterizes the network structure of the construction industry as two-fold; the industry has tight relationship networks within the projects, and a much looser network structure between the parent companies and projects and between different construction stakeholders. This means that within a project each stakeholder and activity is dependent on one another.…”
Section: Construction Industry Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction project organizations thus often become disconnected from the company level and hard to manage and integrate throughout the process, from drawings to finished building. Gadde, 2000, 2002;Karrbom Gustavsson and Gohary, 2012;Karrbom Gustavsson and Hallin, 2015;Kristiansen, et al, 2005;London and Kenley, 2001) Dubois and Gadde (2002) characterizes the network structure of the construction industry as two-fold; the industry has tight relationship networks within the projects, and a much looser network structure between the parent companies and projects and between different construction stakeholders. This means that within a project each stakeholder and activity is dependent on one another.…”
Section: Construction Industry Contextmentioning
confidence: 99%
“…Adding to the transport related coordination problems of urban construction, is the interorganizational relationships within the construction industry itself. Construction in general is produced on a project basis in temporary organizations, where the project organizations often become disconnected from the company level and hard to manage and integrate Gadde, 2000, 2002;Karrbom Gustavsson and Gohary, 2012;Karrbom Gustavsson and Hallin, 2015). Dubois and Gadde (2002) argue that within construction projects, the couplings between different stakeholders and activities on-site are characterized as tight, meaning that within a project each stakeholder and activity is dependent on one another.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale infrastructure organizations are known for rigid boundaries between processes, functions and stakeholders (Gustavsson and Gohary, 2012). These boundaries inhibit knowledge exchange and cooperation across projects implemented by the supply chain.…”
Section: Knowledge Management Theorization In Management and For Projmentioning
confidence: 99%
“…Ethnic culture shapes their character, so that wherever they are, this cultural background greatly influences their character. A recent study conducted by Gustavsson and Gohary (2012) found that there was a wide range of boundaries encompassing facilitated activities and activities pursued during the design and production process, with three boundary range patterns having particular importance in efficient collaboration: geographical boundaries, professional boundaries and stakeholder boundaries. This study complements the concept of the boundary range with the addition of a cultural spanning boundary.…”
Section: Main Platform For Creating Collaboration Of Partiesmentioning
confidence: 99%